Hierarchically Ordered Monolithic Silica with Bimodal Porosity Obtained by Hydrolysis and Condensation of 1, 4‐Bis(trimethoxysilyl)arenes. Issue 11 (8th October 2013) - von der Lehr, Martin; Weidmann, Christoph; Mascotto, Simone; Smarsly, Bernd M.
Abstract 1, 4‐Bis(trimethoxysilyl)benzene and 1, 4‐bis((trimethoxysilyl)‐phenyl)‐dimethoxysilane were synthesized from their corresponding diarylbromides. These bis(trimethoxysilyl)arenes were used as organosilica precursors for the preparation of macro‐/mesoporous silica monoliths, using poly(ethylen glycol) as a porogen to obtain a well‐defined bicontinuous macroporosity and mesoporosity. The porosity of the prepared materials was characterized by nitrogen sorption measurements, mercury intrusion and scanning electron microscopy. The incorporation of silylarenes was studied by solid‐state 13C NMR spectroscopy, IR spectroscopy and elemental analysis.